EFEKTIVITAS METODE SNOWBALL THROWING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MATERI KISAH NABI MUHAMMAD SAW DI SDN 77/III MUKAI TINGGI - Ulsy, Felsy; Nosi Qadariah; Hadi Candra; Albertos Damni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student learning motivation in the Islamic Religious Education (PAI) subject—specifically regarding the topic of the Life of Prophet Muhammad (PBUH)—poses a challenge that can hinder student engagement and the achievement of learning objectives. Therefore, it is necessary to implement teaching methods capable of creating an active, interactive, and enjoyable learning atmosphere. This study aims to analyze the effectiveness of the Snowball Throwing method on the learning motivation of fourth-grade students at SDN 77/III Mukai Tinggi. The study employed a quantitative approach using an experimental method and a pretest-posttest control group design. The sample consisted of 28 students, comprising 13 students in the control group and 15 students in the experimental group. Data were collected through learning motivation questionnaires and observations, then analyzed using validity tests, homogeneity tests, and the Independent Sample t-test. The results indicate a significant difference between the experimental and control groups, with a Sig. (2-tailed) value of 0.001 (p < 0.05). The mean learning motivation score in the experimental group (83.53) was higher than that of the control group (67.38). Increased motivation was evidenced by greater student engagement in discussions, asking and answering questions, and collaboration during the learning process. Thus, the Snowball Throwing method proved effective in enhancing student learning motivation in Islamic Religious Education lessons covering the Life of Prophet Muhammad (PBUH) and can serve as an innovative alternative teaching strategy in primary schools.